Generation of an Enhancer-Trapping Vector for Insertional Mutagenesis in Zebrafish - Liu, Chunyan (PLoS One, 2015)
Enhancer trapping (ET) is a powerful approach to establish tissue- or cell-specific reporters and identify expression patterns of uncharacterized genes. Although a number of enhancer-trapping vectors have been developed and a large library of fish lines with distinct tissue- or cell-specific expression of reporter genes have been generated, the specificity and efficiency of trapping vectors need to be improved because of the bias interaction of minimal promoters with genomic enhancers. Accordingly, we generated an enhancer-trapping vector pTME that contains a minimal mouse metallothionein gene (mMTI) promoter upstream of EGFP reporter. In the first round of screening, twelve zebrafish lines that carry a single copy of ET cassettes were characterized to have tissue- or cell-specific EGFP expression. One of the highly conserved noncoding elements near an insertion site of trapping cassettes was characterized as an enhancer that can specifically regulate the expression of EGFP in cells of the central nervous system. In addition, the pTME vector contains a mutation-cassette that is able to effectively block the transcription of an endogenous gene in an ET line with ubiquitous EGFP expression. Thus, the pTME vector can be used as an alternative tool for both enhancer trapping and mutagenesis across a target genome.